The Texts of the white Yajurveda translated with a popular commentary - Griffith, Ralph T. H. (Banaras Medical Hall Press, 1975)
Philosophy, Vedas, Hinduism, Yajurveda, India
Keywords: Vedic literature; Vedas -- Rgveda; Philosophy -- India; Yajurveda; Hinduism -- Sacred books